Application of Fenton and solar photo-Fenton processes to the treatment of a sanitary landfill leachate in a pilot plant with CPCs - Vítor Vilar (2012)
This paper reports on landfill leachate treatment by Fenton (Fe(2+)/H(2)O(2)) and solar photo-Fenton (Fe(2+)/H(2)O(2)/UV) processes in a pilot plant with compound parabolic collectors (CPCs). The solar photo-Fenton reaction is much more efficient than the respective dark reaction under identical experimental conditions, leading to 86% mineralization and 94% reduction of aromatic content of the leachate after 4 days of solar exposure (206 kJ(UV) L(-1)), consuming 366 mM of H(2)O(2) in the presence of 20 mg L(-1) of iron. According to activated sludge respirometry, BOD(5)/COD ratio, Zahn-Wellens and kinetic results, the amount of UV energy necessary to reach a biodegradable effluent is 113 kJ(UV) L(-1), consuming 227 mM of H(2)O(2), which means almost 73% mineralization of the leachate.